PENGELOLAAN PEMBELAJARAN MENGHAFAL AYAT AL-QUR’AN SECARA CEPAT DENGAN STRATEGI PERMAINAN CROSSWORD PUZZLE - Syarifuddin Khardi (Tarbawi, 2017)
One of the learning strategies that can be applied to the subjects of Islamic Education and Budi Pekerti is the strategy of crossword puzzle. This strategy allows learners to learn optimally, because this strategy is one model of active learning, fun and resembles the play of words through composing verses of mufradat into a whole verse. The purpose of this material is as an answer to the teachers so that learners more quickly memorize the verses of the Qur'an on the subjects of Islamic Education and Character especially on the aspects of the Qur'an. From the results of the description that the application of learning with crossword puzzle strategy is very helpful for teachers and students in memorizing Qur'anic verses according to the material on aspects of the Qur'an and greatly give positive and significant influence with learning outcomes, the learning model of crossword This puzzle can be used as a teacher model of learning in class. Keywords. Learning Model, Crossword Puzzle, Learning Result